Upside of Evidence by Public Prosecutor in The Case Corruption by Act No. 31 of 1999 jo. Act No. 20 of 2001 on Combating Crime of Corruption - Suwono Suwono; Jawade Hafidz (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Corruption is a criminal offense that is remarkable. Remarkable because the mode used increasingly sophisticated, and as a result of corruption is very detrimental to the people and the state. Corruptor often me-take advantage of legal loopholes. Reverse authentication system implemented in the Act No. 31 of 1999 jo. Act No. 20 of 2001 on Corruption Eradication easier for prosecutors to prove that the defendant has committed the crime of corruption. In the system of proof, the defendant has the obligation to prove that the defendant did not commit corruption, and prosecutors also continue to prove that the defendant engaged in corruption cases.Keywords: Upside Evidence; Prosecution; Corruption.